Activation and regulation of IL-1β family of cytokines by EV71 infection - Aw, Ashley Jong Ghut (2014)
Severe cases of hand, foot and mouth disease (HFMD) are usually caused by Enterovirus 71 (EV71) and linked to elevated levels of cytokines. In this study, we first tested the ability of EV71 (BrCr and WD strain) in infecting differentiated monocyte lymphoma (U937) cells, epithelial lung cancer (A549) cells and liver cancer (HUH7) cells. We found that both EV71 strains only infected A549 and HUH7 cells. While EV71 could not infect differentiated U937 cells, the transfection of purified viral RNA into these cells enabled viral replication. We next measured the levels of cytokines IL-1β, IL-8 and IL-18 at different time points after EV71 infection or transfection. We detected (i) IL-1β in EV71 transfected differentiated U937 cells, (ii) IL-18 in EV71 transfected differentiated U937 cells and infected HUH7 cells, and (iii) IL-8 in all three infected/transfected cell types. Additionally, we found upregulation of IL-1β and IL-18 levels in these cells, correlating with viral mRNA levels. While IL-8 upregulation in infected A549 and HUH7 cells correlate with viral mRNA levels, it showed negative correlation with viral mRNA level in transfected differentiated U937 cells. We anticipate that the study of cytokine kinetics in EV71 infected cells would facilitate the understanding of EV71 pathogenesis.